Philippe Raynaud, la philosophie politique de l'école et la formation des enseignants. Un regard à l'aune de l'individualisme démocratique - Camille Roelens (Nantes Université, 2021)
The purpose of this article is to propose an overview of contributions to the public debate of the philosopher Philippe Raynaud, regarding the confrontation of the scholar institution with democratic individualism. Thinking the French educational model and its recent transformations is Raynaud's primary concern, and through this prism he draws a political philosophy of school, whose characteristic features are shown in our article (1.1). We then dedicate a specific study time to the question of teacher's training, which is a crystallization point of his preoccupations and opinions on school policy (1.2). Raynaud's analytical and argumentative approach seems to be built as a potential response to certain concerns about the effects of a neo-Tocquevillian democratic individualism in education. As far as we are concerned, this watchword apparently impossible to elucidate and what it means today for the individual, by the individual and for the individual can be partially dissipated (2).